Exploring the determinants of exclusive breastfeeding among infants under-six months in Ethiopia using multilevel analysis. - Shambel Aychew Tsegaw; Yeshimebet Ali Dawed; Erkihun Tadesse Amsalu (PLoS ONE)
Introduction Exclusive breastfeeding (EBF) is the safest and healthiest option of feeding among infants in the first 6 months throughout the world. Thus, the promotion of EBF is essential to prevent complex infant health problems even at the adulthood level. But the majority of previous studies focused on individual- level determinants of EBF by using basic regression models in localized areas. This study aimed to identify the determinants of EBF at the individual and community level which would be helpful to design appropriate strategies for improving the practice of EBF. Methods It is a secondary data analysis using the 2016 Ethiopian Demographic and Health Survey (EDHS) data. A total of 1185 infants under 6 months of age were included in the analysis. A Multilevel logistic regression model was employed to investigate factors significantly associated with EBF among under-six infants in Ethiopia. Adjusted odds ratio (AOR) with 95% confidence interval (CI) was used to measure the association of variables whereas Intracluster correlation (ICC), median odds ratio (MOR), and proportional change in variance (PCV) were used to measure random effects (variation). Result In multilevel logistic regression; 4-5 months age infant (AOR = 0.04, 95%CI:0.02-0.07), female infants (AOR = 2.51, 95%CI:1.61-3.91), infant comorbidities (AOR = 0.35, 95%CI: 0.21-0.57), richest household wealth index (AOR = 10.34, 95%CI: 3.14-34.03) and antenatal care (AOR = 2.25, 95%CI:1.32-3.82) were individual- level determinants significantly associated with exclusive breastfeeding. Whereas, contextual region (AOR = 0.30, 95%CI: 0.10-0.87), community- level of postnatal visit (AOR = 2.77, 95%CI: 1.26-6.58) and community -level of maternal employment (AOR = 2.8, 95%CI: 1.21-6.47) were community level determinants significantly associated with EBF. The full model showed that46.8% of the variation of exclusive breastfeeding was explained by the combined factors at the individual and community levels. Similarly, it showed that the variation in exclusive breastfeeding across communities remained statistically significant (ICC = 8.77% and variance = 0.32 with P<0.001). Conclusion and recommendation Our study showed that both individual and community level determinants were significantly associated with EBF practice among under 6 infants. Based on our findings, it is recommended to promote and enhance antenatal and postnatal care services utilization of mothers to improve exclusive breastfeeding practice and more emphasis should be given to infants with comorbid conditions and those who were living in the pastoralist regions.